THE PROBLEM OF MOTION PLANNING FOR VEHICLES 0R ROBOTS - Raffo L., Eduardo (2002)
The article is an introduction to the study of the problem of the planning of the movement of a vehicle or robot. For it, first thinks about a solution to determine the difficulty of the terrestrial one and then to plan then movement lo continue inside him.